Profil Usaha Pengolahan â€œCap Tikusâ€ di Desa Tokin Baru Kecamatan Motoling Timur - Susan D. Wala; Olfie L.S. Benu; Mex F.L. Sondakh; Lyndon R.J. Pangemanan (Universitas Sam Ratulangi, 2013)
ABSTRACTSusan Wala. The Profile of â€œCap Tikusâ€ Processing Industry in Tokin Baru Village East Motoling Sub District. Under guidance of Benu Olfie L.S., as chairman, and Mex F.L Sondakh and L.R.J. Pangemanan as members.The objective of this research is to describe the profile of â€œcap tikusâ€ processing industry, based on farmers characteristic, industry condition, industry impact to families welfare and cap tikus farmerâ€™s interaction in society. Method used in this research is census method. This research uses primary and secondary data. Primary data are obtained from interviewed with â€œcap tikusâ€ farmers using questioner to collect the data. Secondary data are obtained from village government/administration office. For describe cap tikus farmers in Tokin baru Village, the data analysis used is descriptive analysis and presented in table form. To calcute cap tikus farmerâ€™s income rate, it uses income analysis followed by R/C analysis to find the feasibility rate of this industry.Cap tikus industry in Tokin Baru Village characterized as home industry (family business) which most of the resources, such as labour and raw materials are from family resources except some fixed active buyed by family. The main problem in this bussines is unstabil prices and the decreased of mayang quality caused by aren tree becoming old. But, the market demands never slack and the ability from farmers who only experts to processing cap tikus make this industry still hold in. This research shows that cap tikus processing industry at Tokin Baru is profitable with R/C ratio 13,02, but if input the calculated cost but not being spend, so the R/C ratio is 0,85. That being held to describe bussines performance in form of bussines managerial evaluation.